PELATIHAN PENYUSUNAN KONTEN MEDIA SOSIAL BAGI PEMUDA DESA UNTUK PROMOSI WISATA DESA WONOKITRI - Yascya, Marcya Nurfarida; Widyowati, Weny (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
The training activity for preparing social media content for young people to promote tourism in Wonokitri Village is integrated with the Gerak Milenial program series which involves the participation of students from various universities individually as facilitators or instructors. This training activity is a medium that provides opportunities for Wonokitri Village youth to learn from students and vice versa, students can learn from the community directly. In this case, students can develop thinking in helping to find solutions to problems that occur in the lives of local communities. Through analysis of the situation and conditions in the field, it was found that efforts to promote village potential were still very lacking, especially the lack of involvement of village youth. The younger generation is expected to be more technologically literate and more easily utilize this technology to help improve tourism promotion. To improve these abilities, especially in the use of cell phone technology with its various applications, the author was involved in training in preparing social media content targeting the younger generation in Wonokitri Village so that they could hone their abilities in creating creative social media content to promote the tourism potential of Wonokitri Village. The training was attended by eleven village youth who were provided with a pre-test, material, and a simple post-test. Through this training, participants realized the importance of creating content on social media as an effort to attract tourists to visit Wonokitri Village.